The Sequin Illusion. (November 2019) - Kuo, Yi-Tsen; Tseng, Philip
The Sequin Illusion can be seen when shapes are drawn in dotted lines, against a background of different brightness. This can be done either with bright dots over a dark background or with dark dots over a bright background, though the latter usually works better. The illusion appears as a wave of dark (or bright) spots inside the dotted shapes (like sequins!) in peripheral vision. Although similar in appearance with the Hermann Grid, the Sequin Illusion occurs inside the shapes; persists despite slanted, disrupted, or nonrectangular edges; and is only eliminated when the dotted contour is formed by colors of similar brightness. Therefore, this illusion is driven by brightness (not color) contrasts in contours, which possibly points to the magnocellular channel in lateral geniculate nucleus.